1998
DOI: 10.1007/s002130050628
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine metabolism rate as a possible index of drug-induced granulocytopenia

Abstract: A possible relationship between haematological adverse reactions and clozapine (CLZ) metabolism rate was studied. Sixteen chronic schizophrenic outpatients (mean age 34.62 years +/- 7.56 SD) were treated with CLZ, 75-600 mg/daily for 9 weeks. CLZ and norclozapine (NCLZ) plasma levels were determined weekly, contemporarily with blood cell counts. CLZ plasma levels ranged from 25 to 1270 ng/ml (mean 266.27 ng/ml +/- 197.44 SD), while NCLZ plasma levels ranged from 25 to 1280 ng/ml (mean 169.0 ng/ml +/- 127.94 SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…It is unclear whether clozapine plasma levels are associated with development of neutropenia. 3234 One of the best-supported hypotheses to explain clozapine’s association with agranulocytosis relates to the bioactivation of clozapine, or a stable metabolite, to a chemically reactive nitrenium ion. 35 The propensity for nitrenium ions to cause apoptosis to neutrophils, or be toxic to neutrophil precursors, is dose dependent, lending support to the hypothesis that clozapine pharmacokinetics and bioavailability are related to its potential to cause neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether clozapine plasma levels are associated with development of neutropenia. 3234 One of the best-supported hypotheses to explain clozapine’s association with agranulocytosis relates to the bioactivation of clozapine, or a stable metabolite, to a chemically reactive nitrenium ion. 35 The propensity for nitrenium ions to cause apoptosis to neutrophils, or be toxic to neutrophil precursors, is dose dependent, lending support to the hypothesis that clozapine pharmacokinetics and bioavailability are related to its potential to cause neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological mechanism of agranulocyotosis is uncertain, but hypotheses include a direct toxic effect on neutrophils or haemopoietic precursors (Veys et al, 1992;Gerson et al, 1994;Deliliers et al, 1998), and an immunological basis (Pisciottta et al, 1992), the latter with a possible genetic predisposition (Lieberman et al, 1990;Corzo et al, 1995). Desmethylclozapine at high concentrations has been seen to have a toxic effect on the precursors of both myeloid and erythroid lineages (Gerson et al, 1994), and the desmethylclozapine/clozapine ratio has been seen to be inversely correlated with neutrophil count in patients treated with clozapine (Mauri et al, 1998). If the formation of Motor impairment in the mice was rated using the criteria given in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies were performed in a small or small to medium size sample, ranging from 6 to 190 patients receiving clozapine. Correlation of clozapine or metabolite levels with dose was calculated in thirteen studies [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]; nine reported a positive correlation between dose and plasma clozapine levels alone or with metabolite levels as well [ 34 , 35 , 36 , 37 , 39 , 41 , 42 , 43 , 44 ] and two reported no correlation with clozapine and norclozapine levels [ 45 , 46 ]. Sporn et al [ 40 ] found a positive correlation of clozapine dose with norclozapine but not clozapine plasma levels, and Mauri et al [ 38 ] reported that clozapine dosage correlated with clozapine but not norclozapine plasma levels.…”
Section: Resultsmentioning
confidence: 99%
“…Correlation of clozapine or metabolite levels with dose was calculated in thirteen studies [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]; nine reported a positive correlation between dose and plasma clozapine levels alone or with metabolite levels as well [ 34 , 35 , 36 , 37 , 39 , 41 , 42 , 43 , 44 ] and two reported no correlation with clozapine and norclozapine levels [ 45 , 46 ]. Sporn et al [ 40 ] found a positive correlation of clozapine dose with norclozapine but not clozapine plasma levels, and Mauri et al [ 38 ] reported that clozapine dosage correlated with clozapine but not norclozapine plasma levels. Furthermore, 27 studies examined the correlation of clozapine dose with adverse effects; of them, 19 found no correlation between dose and side effects studied [ 22 , 35 , 36 , 37 , 38 , 41 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ,…”
Section: Resultsmentioning
confidence: 99%